Preparation method of quick-hardening super-early-strength three-dimensional flexible composite coiled material
Through the synergistic effect of modified 3D spaced fiber fabric and gelled powder mixture, the problems of long curing time and low strength of concrete canvas are solved, and the preparation of fast-hard, ultra-premature and strong three-dimensional flexible composite coil is achieved, satisfying the temporary road High intensity demand for emergency repairs and heavy-load traffic pavements.
Patent Information
- Application Number
- CN202411145021.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-20
- Publication Date
- 2024-12-31
AI Technical Summary
Due to the long curing time of gelling powder mixture, existing concrete canvas is difficult to quickly achieve high strength in emergency scenarios such as temporary road repairs, which limits its application in road paving.
Using the synergistic effect of modified 3D spacer fiber fabric and gelling powder mixture, the fiber is treated by the interface modifier aqueous epoxy resin, combining specific ratio gelling materials, gypsum, mineral blends, aggregates and additives The fast hard super early strength three-dimensional flexible composite coil is prepared to achieve rapid hardening and high strength of gelled powder mixture.
It reaches high strength in a very short time, with initial settling time <20 minutes, compressive strength ≥40MPa in 1.5 hours, and flexural strength ≥7.5MPa. It is suitable for temporary road emergency repair and heavy traffic pavement, meeting the needs of rapid laying and high-strength .
Smart Images

Figure CN119217803A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a concrete material, in particular to a method for preparing a fast-hardening, ultra-early-strength three-dimensional flexible composite coiled material. Background Art
[0002] Concrete canvas is a new type of building material, which is mainly composed of 3D spacer fiber fabric and hydraulic cement powder material. It can be used after being spread out and watered during construction. It has the advantages of easy storage and transportation, convenient construction, etc. It is often used in scenes such as slope river protection and ditch reinforcement. The existing rapid laying processes of temporary roads include cement concrete assembled pavement, prefabricated road panels, asphalt concrete pavement, dry hard concrete pavement, etc. The above methods all have problems such as complex construction process, high construction difficulty, high construction cost and long construction period. As a temporary road paving material, concrete canvas is easy to lay, has a short construction time, and has excellent toughness and load-bearing capacity. However, the existing concrete canvas generally needs to be cured at room temperature for one day to have high strength because the internal cement powder mixture takes too long to cure after watering. For scenes where concrete canvas needs to be put into use within one or two hours, such as temporary road repair and emergency rescue, the existing concrete canvas is difficult to meet their needs, which limits the use of concrete canvas in road paving to a certain extent. Summary of the invention
[0003] In order to overcome the problem in the prior art that the cementitious material has a slow setting time and low curing strength during the curing process of concrete canvas, resulting in a long waiting time for actual use of the concrete canvas after laying, the present invention provides a method for preparing a fast-hardening ultra-early-strength three-dimensional flexible composite coil. The present invention encapsulates the cementitious powder mixture into a modified 3D spacer fiber fabric, and through the synergistic effect of the two, the preparation of the fast-hardening ultra-early-strength three-dimensional flexible composite coil is achieved, thereby solving the problem of slow setting speed and low strength of concrete canvas.
[0004] The objective of the present invention is achieved through the following technical solutions:
[0005] A method for preparing a fast-hardening, ultra-early-strength three-dimensional flexible composite coil comprises the following steps:
[0006] Step (1) selects high-strength fibers to make 3D spacer fiber fabrics as double-layer sandwich frames of quick-hardening ultra-early-strength three-dimensional flexible composite coils, wherein:
[0007] The double-layer sandwich frame is composed of a dense woven layer and a sparse woven layer. The dense woven layer is used as the upper layer of the quick-hardening ultra-early-strength three-dimensional flexible composite coil to ensure that the powder is not exposed and that water can penetrate. The sparse woven layer is a fiber woven mesh with a hole diameter of about 3 mm, which is convenient for filling the gel powder mixture. The dense woven layer and the sparse woven layer are connected into a whole through longitudinal fiber monofilaments.
[0008] The high-strength fiber is a blend of one or more of carbon fiber, polyester fiber, aramid fiber, glass fiber, polypropylene fiber, and basalt fiber;
[0009] The 3D spacer fiber fabric needs to have good adhesion, stress stability and durability to ensure the common stress between the fabric and the cement matrix and increase the initial strength. Therefore, the surface of the longitudinal fiber monofilaments of the 3D spacer fiber fabric is modified by using an interfacial modifier, water-based epoxy resin;
[0010] Step (2) fills the gelled powder mixture into the 3D spacer fiber fabric, vibrates and fills it, and compacts it to serve as the sandwich layer of the quick-hardening, ultra-early-strength three-dimensional flexible composite coil, wherein:
[0011] The cementitious powder mixture is calculated by the following weight parts, and is mixed with 87-91 parts of cementitious materials, 10-20 parts of gypsum, 0.5-3 parts of mineral admixtures, 1-3 parts of aggregates, 3-6 parts of fibers, and 0.5-3 parts of admixtures. The functions of the cementitious materials, mineral admixtures, and admixtures are to regulate the setting time and improve the early strength. The functions of the aggregates and fibers are to further improve the ultra-early strength of the powder mixture. The obtained fast-hardening and ultra-early-strength three-dimensional flexible composite coiled material can have the function of fast-hardening and ultra-early-strength after being sprinkled, immersed, or soaked in water on the surface of the concrete canvas when in use;
[0012] The cementitious material is a mixture of one or more of silicate cement (including silicate cement, ordinary silicate cement, slag silicate cement, fly ash silicate cement, pozzolanic silicate cement and composite silicate cement), sulphoaluminate cement, aluminate cement and phosphate cement, and its strength grade can be 42.5, 42.5R, 52.5, 52.5R, 62.5 and 62.5R;
[0013] The gypsum is one of α-hemihydrate gypsum, β-hemihydrate gypsum, anhydrous gypsum, dihydrate gypsum or phosphogypsum, and the gypsum can react with CAH to form ettringite, which reduces the setting time, fills the capillary pores and microcracks in the sample, and improves the density of the sample;
[0014] The mineral admixture is a composite of one or more of silica fume, fly ash, mineral powder and quicklime. The main purpose of adding the mineral admixture is that the gelling or pozzolanic components in the mineral admixture react with cement to form a gelling hydration product, such as CSH gel, so as to improve the internal structure of the concrete and increase the strength.
[0015] The aggregate is a composite of river sand, machine-made sand, quartz sand, quartz powder, and corundum. The purpose of adding the aggregate is to further enhance the strength of the cementitious powder mixture. The particle size is ≤3 mm to ensure that the mixture can be filled into the 3D spacer fiber fabric after being prepared.
[0016] The fiber is one of glass fiber, polypropylene fiber, basalt fiber and steel fiber, and its length should be smaller than the grid size of the three-dimensional sandwich frame. It is dispersed in the cementitious composite material. The fiber can effectively control the micro cracks caused by factors such as plastic shrinkage, dry shrinkage and temperature change of cement-based materials, prevent and inhibit the formation and development of original cracks in concrete, and improve the mechanical properties of cement-based materials.
[0017] The admixture is two or more of a water reducer, an early strength agent, an antifreeze agent, and a modifier, wherein the water reducer is one of a naphthalene-based water reducer, a polycarboxylic acid water reducer, and a melamine water reducer, and the water reducer can reduce the adhesion between cement particles and water, enhance the fluidity of concrete, and improve the strength and durability of concrete; the early strength agent is one of lithium carbonate, calcium chloride, sodium sulfate, and aluminum sulfate, and the main function of the early strength agent is to accelerate the hydration rate of cement and promote the development of early strength of concrete; the antifreeze agent is a compound of two or more of chlorides, nitrates, and nitrites to form a The composite antifreeze agent; the modifier is one or more of nano sodium silicate powder and nano calcium silicate. The mechanism of action of nano calcium silicate is to induce CSH nucleation in the early stage of cement hydration, greatly improve the hydration reaction process, and significantly improve the early strength of cement-based products, especially the ultra-early strength within 10 hours, which is particularly suitable for low-temperature construction in winter. After adding nano calcium silicate, the setting time of the cementitious powder mixture is between 10 and 15 minutes, and the compressive strength of 1.5 hours can reach 55 to 60 MPa, and the flexural strength can reach 5 to 8 MPa.
[0018] Step (3) The packaging cloth is coated with packaging glue and hot-pressed at 50-80° C. to be laminated to the sparse woven layer of the 3D spacer fiber fabric as the bottom layer of the quick-hardening, ultra-early-strength three-dimensional flexible composite coil, wherein:
[0019] The packaging cloth is one of carbon fiber cloth, glass fiber cloth, polypropylene fiber cloth and basalt fiber cloth, and the packaging glue is a conventional epoxy adhesive. The waterproof packaging cloth can not only seal the filled gelling powder mixture to prevent the powder from overflowing, but also prevent moisture from seeping from the bottom when sprinkling water, affecting the early strength of the quick-hardening and ultra-early-strength three-dimensional flexible composite coil.
[0020] The specific method of using the quick-hardening, ultra-early-strength three-dimensional flexible composite coil prepared by the above method is: watering the surface of the quick-hardening, ultra-early-strength three-dimensional flexible composite coil with a water-to-material ratio of 0.35 to 0.4, or taking it out after immersing it in water for 20 to 50 seconds. The quick-hardening, ultra-early-strength functional characteristics obtained are: initial setting time <20min, final setting time <30min, 1h compressive strength ≥30MPa, 1h flexural strength ≥5MPa; 1.5h compressive strength ≥40MPa, 1.5h flexural strength ≥7.5MPa.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] 1. The cementitious powder mixture obtained by using the orthogonal mix ratio of cementitious materials, early strength agent, and nano modifier has the characteristics of super-fast hardening and super-early strength after stirring. Through the compounding effect of early strength agent, modifier and cementitious materials, it can solidify and harden in a very short time, generate hydrated calcium silicate gel and calcium aluminate, and release a lot of heat, which is conducive to the use of fast-hardening, super-early strength three-dimensional flexible composite coil in low temperature environment.
[0023] 2. Compared with the common method of adding redispersible rubber powder into the cementitious material, the present invention uses an interfacial modifier, water-based epoxy resin, to perform surface modification on the longitudinal fiber monofilaments of the 3D spacer fiber fabric, so that the adhesion between the cementitious powder mixture and the 3D spacer fiber fabric is better after hardening, and will not affect the ultra-early strength of the cementitious material itself.
[0024] 3. The setting time of the fast-hardening ultra-early-strength three-dimensional flexible composite coil prepared by the present invention is within 30 minutes, the 1.5h strength exceeds 50% of the ultimate strength, and the 3d strength is close to the ultimate strength, reaching the ultra-early strength standard. According to the "Technical Specifications for Highway Cement Concrete Pavement Construction", for heavy-load traffic pavements, the 3d flexural strength is required to be not less than 4.5MPa and the compressive strength is not less than 25.5MPa. Therefore, the fast-hardening ultra-early-strength three-dimensional flexible composite coil prepared by the present invention is suitable for temporary paving, repair and construction of engineering projects. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 1 is a schematic diagram of the structure of the medium-speed hard ultra-early strong three-dimensional flexible composite coiled material of Examples 1 to 3, in which 1 is a densely woven surface, 2 is a sparsely woven surface, 3 is a spacer sand I, and 4 is a spacer sand II;
[0026] Figure 2 This is a microscopic picture of the hardening of the gelled powder mixture before and after the addition of nano calcium silicate in Example 4. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is further described below in conjunction with the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0028] Comparative Example
[0029] A method for preparing a fast-hardening, ultra-early-strength three-dimensional flexible composite coil is completed by the following steps:
[0030] (1) Glass fiber is selected to make 3D spacer fiber fabric as a double-layer sandwich frame of the rapid hardening ultra-early strength three-dimensional flexible composite coil. One layer is a dense woven layer, which serves as the upper layer of the rapid hardening ultra-early strength three-dimensional flexible composite coil to ensure that the powder is not exposed and that water can penetrate. The other layer is a sparse woven layer, which is a fiber woven mesh with a pore size of about 3 mm, which is convenient for filling the gel powder mixture. The upper and lower layers are connected into a whole by longitudinal fiber monofilaments. Figure 1 .
[0031] In this comparative example, the thickness of the quick-hardening, ultra-early-strength three-dimensional flexible composite coil is 13 mm.
[0032] (2) A gelled powder mixture is selected and filled into the 3D spacer fiber fabric, which is then vibrated and compacted to serve as the sandwich layer of the quick-hardening, ultra-early-strength three-dimensional flexible composite coil.
[0033] In this embodiment, the main preparation process of the cementitious powder mixture is: select 60 parts of 62.5 sulphoaluminate cement, 20 parts of aluminate cement, 10 parts of α high-strength semi-hydrate gypsum and 8 parts of 52.5R silicate cement as the main cementitious materials, first add 3 parts of quartz sand and quartz powder with a particle size of ≤3mm, the ratio is 16:21; then add 5 parts of steel fiber with a length of 3mm to weaken the stress concentration effect of internal pores, cracks and other defects of the material, thereby improving the strength of the material; then add 0.5 parts of silica fume to the cementitious material to fill the internal pores of the matrix hardening, improve the interface structure and bonding force of the matrix, and enhance the density of the matrix; finally, add 0.3 parts of polycarboxylic acid high-efficiency water reducer and 0.2 parts of lithium carbonate to obtain a cementitious powder mixture.
[0034] (3) Water-impermeable glass fiber packaging cloth is selected and coated with conventional epoxy adhesive and hot-pressed at 60°C to form a sparse woven layer of 3D spacer fiber fabric as the bottom layer of the quick-hardening, ultra-early-strength three-dimensional flexible composite roll. The water-impermeable glass fiber packaging cloth not only has the function of sealing and retaining water, but also can significantly improve the early flexural strength of the quick-hardening, ultra-early-strength three-dimensional flexible composite roll.
[0035] After the packaging is completed, the specific method of use of the comparative example is: watering the surface of the quick-hardening ultra-early-strength three-dimensional flexible composite coil, with a water-to-material ratio of 0.35, or taking it out after immersing it in water for 20 to 50 seconds. The obtained quick-hardening ultra-early-strength functional characteristics are: initial setting time of 18 minutes, final setting time of 27 minutes, 1h compressive strength of 25MPa, 1h flexural strength of 5.1MPa; 1.5h compressive strength of 32MPa, 1.5h flexural strength of 6.3MPa.
[0036] Example 1
[0037] The difference between this embodiment and the comparative example is that an interfacial modifier is used to perform surface modification treatment on the longitudinal fiber monofilaments of the 3D spacer fiber fabric, and the main steps are: first, a low-viscosity water-based epoxy resin is prepared and placed in a flat container with a solution height of about 10 mm; then, the 3D spacer fiber fabric is laid flat with the sparse-woven surface facing down and immersed for 60 seconds, and the longitudinal fiber monofilaments are taken out after being fully immersed; finally, it is placed at room temperature to dry for use, and the main purpose of drying is to prevent the dense-woven surface from being immersed in the water-based epoxy resin.
[0038] The rapid-hardening and ultra-early-strength three-dimensional flexible composite coil prepared in this embodiment has the following rapid-hardening and ultra-early-strength functional characteristics: initial setting time is 16 min, final setting time is 25 min, 1h compressive strength is 29 MPa, 1h flexural strength is 5.5 MPa; 1.5h compressive strength is 35 MPa, 1.5h flexural strength is 7.0 MPa.
[0039] Example 2
[0040] The difference between this embodiment and embodiment 1 is that: on the basis of surface modification treatment of the longitudinal fiber monofilaments of the 3D spacer fiber fabric by the interfacial modifier, 1 portion of nano calcium silicate powder is added into the gelled powder mixture.
[0041] The rapid-hardening and ultra-early-strength three-dimensional flexible composite coil prepared in this embodiment has the following rapid-hardening and ultra-early-strength functional characteristics: initial setting time is 15 min, final setting time is 20 min, 1h compressive strength is 30 MPa, 1h flexural strength is 5 MPa; 1.5h compressive strength is 35 MPa, 1.5h flexural strength is 7 MPa.
[0042] Example 3
[0043] The difference between this embodiment and embodiment 1 is that: on the basis of surface modification treatment of the longitudinal fiber monofilaments of the 3D spacer fiber fabric by the interfacial modifier, 2 parts of powdered nano calcium silicate are added into the gelled powder mixture.
[0044] The rapid-hardening and ultra-early-strength three-dimensional flexible composite coil prepared in this embodiment has the following rapid-hardening and ultra-early-strength functional characteristics: initial setting time is 13 min, final setting time is 17 min, 1h compressive strength is 33 MPa, 1h flexural strength is 6.5 MPa; 1.5h compressive strength is 41 MPa, 1.5h flexural strength is 8.2 MPa.
[0045] Depend on Figure 2 It can be seen that after adding 2 parts of nano calcium silicate powder and a small amount of needle-shaped ettringite attached to the surface, more CSH gel crystals are generated on the surface of cement particles after hydration for 1.5 hours, and some of the needle-shaped ettringite attached to the surface is wrapped by CSH gel to form a dense gel structure.
Claims
1. A method for preparing a fast-hardening, ultra-early-strength three-dimensional flexible composite coil, characterized in that The method comprises the following steps: Step (1) selects high-strength fibers to make 3D spacer fiber fabrics as double-layer sandwich frames of quick-hardening ultra-early-strength three-dimensional flexible composite coils, wherein: The double-layer sandwich frame is composed of a densely woven layer and a sparsely woven layer, and the densely woven layer and the sparsely woven layer are connected into a whole through longitudinal fiber monofilaments; Step (2) fills the gelled powder mixture into the 3D spacer fiber fabric, vibrates and fills it, and compacts it to serve as the sandwich layer of the quick-hardening, ultra-early-strength three-dimensional flexible composite coil, wherein: The cementitious powder mixture is prepared by mixing 87 to 91 parts of cementitious materials, 10 to 20 parts of gypsum, 0.5 to 3 parts of mineral admixtures, 1 to 3 parts of aggregates, 3 to 6 parts of fibers, and 0.5 to 3 parts of admixtures in the following parts by weight; In step (3), the packaging cloth is coated with packaging glue and hot-pressed at 50-80° C. to be compounded on the sparse woven layer of the 3D spacer fiber fabric as the bottom layer of the quick-hardening, ultra-early-strength three-dimensional flexible composite coil.
2. The method for preparing the fast-hardening ultra-early-strength three-dimensional flexible composite coil according to claim 1, characterized in that The densely woven layer serves as the upper layer of the quick-hardening, ultra-early-strength three-dimensional flexible composite coil, and the sparsely woven layer is a mesh of fiber weaving.
3. The method for preparing the fast-hardening ultra-early-strength three-dimensional flexible composite coil according to claim 1, characterized in that The high-strength fiber is a blend of one or more of carbon fiber, polyester fiber, aramid fiber, glass fiber, polypropylene fiber and basalt fiber.
4. The method for preparing the fast-hardening ultra-early-strength three-dimensional flexible composite coil according to claim 1, characterized in that The longitudinal fiber monofilament is surface-modified by using an interfacial modifier, water-based epoxy resin.
5. The method for preparing the fast-hardening ultra-early-strength three-dimensional flexible composite coil according to claim 1, characterized in that The cementitious material is a mixture of one or more of silicate cement, sulphoaluminate cement, aluminate cement and phosphate cement; the gypsum is one of α-hemihydrate gypsum, β-hemihydrate gypsum, anhydrous gypsum, dihydrate gypsum or phosphogypsum; the mineral admixture is one or a composite of silica fume, fly ash, mineral powder and quicklime; the aggregate is one or a composite of river sand, machine-made sand, quartz sand, quartz powder and corundum; the fiber is one of glass fiber, polypropylene fiber, basalt fiber and steel fiber; the admixture is two or more of a water reducer, an early strength agent, an antifreeze agent and a modifier.
6. The method for preparing the fast-hardening ultra-early-strength three-dimensional flexible composite coil according to claim 5, characterized in that The strength grades of the cementitious material are 42.5, 42.5R, 52.5, 52.5R, 62.5, 62.5R; the particle size of the aggregate is ≤3mm; and the length of the fiber is smaller than the grid size of the three-dimensional sandwich frame.
7. The method for preparing the fast-hardening ultra-early-strength three-dimensional flexible composite coil according to claim 5, characterized in that The water reducer is one of naphthalene-based water reducer, polycarboxylic acid water reducer and melamine water reducer; the early strength agent is one of lithium carbonate, calcium chloride, sodium sulfate and aluminum sulfate; the antifreeze agent is two or more of chloride, nitrate and nitrite; the modifier is one or more of nano sodium silicate powder and nano calcium silicate powder.
8. The method for preparing the rapid-hardening ultra-early-strength three-dimensional flexible composite coil according to claim 1, characterized in that The packaging cloth is one of carbon fiber cloth, glass fiber cloth, polypropylene fiber cloth and basalt fiber cloth.
9. The method for preparing the fast-hardening ultra-early-strength three-dimensional flexible composite coil according to claim 1, characterized in that The packaging glue is a special epoxy adhesive.
10. A method for using the fast-hardening ultra-early-strength three-dimensional flexible composite coil prepared by the method according to any one of claims 1 to 9, characterized in that The method of use is as follows: watering the surface of the quick-hardening ultra-early-strength three-dimensional flexible composite coiled material with a water-to-material ratio of 0.35 to 0.4, or taking it out after immersing it in water for 20 to 50 seconds.
